المرويات المرفوعة الواردة في (المُلْتَزَم) في كتب الحديث (تخريج ودراسة) (Journal of the College of Basic Education, 2024)
Almighty God made the Sacred House the Qibla of Muslims, honored it, and made it sanctity in the souls of Muslims, especially for visitors and intending pilgrims and Umrah performers, because of its clear feelings and verses. The focus was on the ritual of (Al-Multazam), which is the place between the Black Stone and the door of the Holy Ka'aba, which Hajj and Umrah pilgrims go to supplicate there. Because it is one of the places in which supplication is answered, so the researcher collected, and studied the "marweyyat" (narrations) that were mentioned in the statement of commitment to supplication in this blessed place in the books of hadith, to clarify its importance to the one who visits the Sacred House of God, The total number of narrations that the researcher reviewed was seven ones